2015
DOI: 10.1038/srep10454
|View full text |Cite
|
Sign up to set email alerts
|

Antennae hold a key to Varroa-sensitive hygiene behaviour in honey bees

Abstract: In honey bees, Varroa sensitive hygiene (VSH) behaviour, which involves the detection and removal of brood parasitised by the mite Varroa destructor, can actively participate in the survival of colonies facing Varroa outbreaks. This study investigated the mechanisms of VSH behaviour, by comparing the antennal transcriptomes of bees that do and do not perform VSH behaviour. Results indicate that antennae likely play a key role in the expression of VSH behaviour. Comparisons with the antennal transcriptome of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 64 publications
(69 reference statements)
2
88
0
1
Order By: Relevance
“…Furthermore, a colony is genetically diverse hence, the activity of individual hygienic bees is not sufficient to meet the increased demand for task performance (Arathi et al 2006). Studies have shown that olfaction plays a role in hygienic behavior (Masterman et al 2000;Plettner et al 2017) and that the origin of VSH behavior is at least partly related to shifts in antennal gene expression (Mondet et al 2015), therefore, olfactory cues might have played a critical role in the expression of VSH behavior in this study. Worker bees may have detected the presence of different densities of mites in brood cells using these cues other than the previously known fertility signals and the response to these chemical signals seem to be additive as highest removal rates were observed for eight or ten mites compared to five mites singly introduced in closely neighboring brood cells.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, a colony is genetically diverse hence, the activity of individual hygienic bees is not sufficient to meet the increased demand for task performance (Arathi et al 2006). Studies have shown that olfaction plays a role in hygienic behavior (Masterman et al 2000;Plettner et al 2017) and that the origin of VSH behavior is at least partly related to shifts in antennal gene expression (Mondet et al 2015), therefore, olfactory cues might have played a critical role in the expression of VSH behavior in this study. Worker bees may have detected the presence of different densities of mites in brood cells using these cues other than the previously known fertility signals and the response to these chemical signals seem to be additive as highest removal rates were observed for eight or ten mites compared to five mites singly introduced in closely neighboring brood cells.…”
Section: Discussionmentioning
confidence: 82%
“…Hygienic bees remove affected brood most likely by detecting odor cues emanating from infested hosts, when these cues exceed the response threshold of the bees within the colony (Masterman et al 2001;Martin et al 2002). Indeed, the transcriptional response in antennal-specific genes suggests a key role for chemical discrimination of mite infested cells (Mondet et al 2015). A detailed description of chemicals involved in the interaction between mites and honey bees has been given by Nazzi and Le Conte (2016).…”
Section: Introductionmentioning
confidence: 99%
“…The annotation of 21 OBPs, 6 CSPs and 170 ORs has contributed some understanding of the peripheral olfactory processing of honey bees (Foret, Wanner, & Maleszka, ; Robertson & Wanner, ). Some information on central olfactory processing in honey bees exists (Galizia, Sachse, Rappert, & Menzel, ) but most studies of honey bee behavioural variation have implicated the peripheral nervous system (Guarna et al, ; Mondet et al, ; Sánchez‐Gracia, Vieira, & Rozas, ) or endocrine organs (Page, Rueppell, & Amdam, ; Ronai et al, ). Affinity and functional assays have established biological function for few CSPs in honey bees, such as OBP1 binding to queen mandibular pheromone (Danty et al, ) and OR11 as a specific receptor of 9‐oxo‐2‐decenoic acid (Wanner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of evidence suggesting that hygienic bees identify diseased brood through olfactory cues891011121314 and that they are more sensitive to and better at discriminating between them814. The antennae, bees’ main olfactory organ15, have been shown to play a pivotal role in HB with multiple independent research groups identifying significantly differentially expressed antennal genes in hygienic versus non-hygienic bees, as well as strong antennal biomarkers for selective breeding913161718.…”
mentioning
confidence: 99%
“…The antennae, bees’ main olfactory organ15, have been shown to play a pivotal role in HB with multiple independent research groups identifying significantly differentially expressed antennal genes in hygienic versus non-hygienic bees, as well as strong antennal biomarkers for selective breeding913161718. Odorant binding protein (OBPs) aid odour detection and are consistently upregulated in hygienic bees’ antennae.…”
mentioning
confidence: 99%